2015
DOI: 10.1177/1465116515581201
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal redistribution and public support for European integration

Abstract: This article contributes to existing debates on public opinion towards European integration by examining when and why fiscal transfers and public support are systematically related. Drawing on economic and identity-related theories, we develop and test hypotheses about the links between EU fiscal transfers among countries and subnational jurisdictions, and citizens' support for European integration. Using a three-level analysis of residents in 143 regions in 16 EU member states, we find a positive effect of EU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 54 publications
11
59
0
Order By: Relevance
“…In this case we found that the importance of these two factors was stronger than that of those that have an EU‐wide influence on EU image, however, they played a role for the negative EU image in some regions only, while being insignificant in others. This finding adds to those from previous studies associating positive attitudes towards the EU and its Cohesion Policy with higher education levels (Chalmers & Dellmuth, ; Dijkstra et al, ; Osterloh, ); however, our results indicate that low education matters for negative EU image only in some clusters of European regions. More research is needed on this to elucidate why there is such a regional differentiation of the importance of this factor.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…In this case we found that the importance of these two factors was stronger than that of those that have an EU‐wide influence on EU image, however, they played a role for the negative EU image in some regions only, while being insignificant in others. This finding adds to those from previous studies associating positive attitudes towards the EU and its Cohesion Policy with higher education levels (Chalmers & Dellmuth, ; Dijkstra et al, ; Osterloh, ); however, our results indicate that low education matters for negative EU image only in some clusters of European regions. More research is needed on this to elucidate why there is such a regional differentiation of the importance of this factor.…”
Section: Resultssupporting
confidence: 85%
“…Answering the research questions, we found that Cohesion Policy—the EU's central investment tool corresponding to one‐third of the EU's budget, managed largely at the regional level and hence “close to the citizens”, and supporting investment that should have a tangible impact on European cities and regions—does matter for EU image at the regional scale. Echoing the findings from previous studies stressing a positive influence of Cohesion Policy on the perceptions of the EU (Chalmers & Dellmuth, ; Osterloh, ), we found that greater amounts of ESIF per capita allocated to regions are inversely related to negative EU image among their citizens. Importantly, the size of the Cohesion Policy funding allocation mattered across our entire sample.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…These micro-level findings should not come a surprise, however, since numerous works have demonstrated that general economic indicators and SIFs have an effect on public opinion towards the EU (see Anderson and Reichert, 1995;Armingeon and Ceka, 2014;Chalmers and Dellmuth, 2015;Dellmuth and Chalmers, 2018). Moreover, EU regional policy can affect parties' support for EU integration (Gross and Debus, 2018).…”
Section: Micro-level Analysismentioning
confidence: 89%
“…The extant literature suggests that the mass attitude toward the European project is affected by the degree of cognitive mobilization and political awareness of individuals. Specifically, it is argued that support for the EU and/or identification with the European project is greater among people who are more conscious of European issues and who are more interested in politics at the European level (Chalmers & Delmuth, ; Clements, ; Gabel, ; Luhman, ). It has been shown that the perception of the EU also varies between individuals with different political values while, at the same time, it can be influenced by the opinion of leaders and parties' political ‘cues’ (Clements, ; Gabel, ; Marks & Hooghe, ).…”
Section: Introductionmentioning
confidence: 99%